2019
DOI: 10.11628/ksppe.2019.22.5.445
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the Saliva Cortisol Concentration and Blood Pressure of Patients with High Blood Pressure and Diabetes After Participating in Agro-healing Activities

Abstract: This study was conducted to find out physical changes in the blood pressure and saliva cortisol of patients with high blood pressure and diabetes after participating in agro-healing activities. The saliva cortisol and blood pressure of 14 males and females aged 49.79±10.48 on average were measured after participating in agro-healing activities. The saliva collection system was used, and their satisfaction level for the program was also surveyed. Changes in the values before and after participating in the agro-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 17 publications
1
0
0
Order By: Relevance
“…However, in the plant preference tendency factor, there was a statistically significant result between the group in their 20s and the group over 60 (p < .05), and the mean of plant gardening activity level tended to be higher as the age increased. This result is supported by Jang et al (2019) who reported in a survey on plant experience and awareness among visitors of a care farming center that older respondents tended to show a higher level of plant growing experience.…”
Section: Plant Experience and Awarenesssupporting
confidence: 53%
“…However, in the plant preference tendency factor, there was a statistically significant result between the group in their 20s and the group over 60 (p < .05), and the mean of plant gardening activity level tended to be higher as the age increased. This result is supported by Jang et al (2019) who reported in a survey on plant experience and awareness among visitors of a care farming center that older respondents tended to show a higher level of plant growing experience.…”
Section: Plant Experience and Awarenesssupporting
confidence: 53%